Determination of Trace Elements in Some Dried Winter Foods - CIFTCI, HARUN; KARPTA, ERGIN (Asian Journal of Chemistry, 2010)
The levels of trace elements in nine food of winter which are grown in Elazig, Turkey were determined. Flame atomic absorption spectrometry (F-AAS) and high performance liquid chromatography (HPLC) were used in this work. The levels of trace metals in food samples were found in the ranges, 60-250, 8.60-58.60, 13.20-44.8, 0.75-3.92, 0.18-0.42 μg g-1 (dry matter) for Fe, Zn, Cu, Ni and Co, respectively. The accuracy and precision of the analysis were checked against the standard reference materials SRM (NIST 1573 a-tomato leaves). The results obtained for Cu, Zn, Fe, Ni and Co were in an excellent agreement with the certified values.